An Efficient Metal–Organic Framework‐Derived Nickel Catalyst for the Light Driven Methanation of CO2. (9th November 2021) - Khan, Il Son; Mateo, Diego; Shterk, Genrikh; Shoinkhorova, Tuiana; Poloneeva, Daria; Garzón‐Tovar, Luis; Gascon, Jorge
Abstract: We report the synthesis of a highly active and stable metal‐organic framework derived Ni‐based catalyst for the photothermal reduction of CO2 to CH4 . Through the controlled pyrolysis of MOF‐74 (Ni), the nature of the carbonaceous species and therefore photothermal performance can be tuned. CH4 production rates of 488 mmol g −1  h −1 under UV‐visible‐IR irradiation are achieved when the catalyst is prepared under optimized conditions. No particle aggregation or significant loss of activity were observed after ten consecutive reaction cycles or more than 12 hours under continuous flow configuration. Finally, as a proof‐of‐concept, we performed an outdoor experiment under ambient solar irradiation, demonstrating the potential of our catalyst to reduce CO2 to CH4 using only solar energy. Abstract : A Ni‐based catalyst derived from Ni‐MOF‐74 was synthesized and studied for the photothermal methanation reaction. The catalyst shows high performance for CH4 production under visible‐IR irradiation. The catalyst also shows high stability and excellent recyclability after several consecutive reaction cycles.